RETRACTED ARTICLE: The LMCD1-AS1/miR-526b-3p/OSBPL5 axis promotes cell proliferation, migration and invasion in non-small cell lung cancer - Rui Hu; Yankai Yu; Haining Wang (BMC Pulmonary Medicine, 2022)
Abstract Purpose To explore the specific role and regulatory mechanism of oxysterol binding protein like 5 (OSBPL5) in non-small cell lung cancer (NSCLC). Methods and results Quantitative real-time polymerase chain reaction (qRT-PCR) analysis demonstrated that OSBPL5 expression was notably elevated in NSCLC tissues and cell lines, and Kaplan–Meier analysis manifested that high OSBPL5 expression was closely related to the poor prognosis of NSCLC patients. Besides, according to the results from western blot analysis, cell counting kit-8, EdU and Transwell assays, knockdown of OSBPL5 suppressed NSCLC cell proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) process. Additionally, by performing qRT-PCR analysis, luciferase reporter and RNA pull-down assays, we verified that OSBPL5 was a downstream target of miR-526b-3p and long noncoding RNA (lncRNA) LMCD1-AS1 served as a sponge for miR-526b-3p. Moreover, from rescue assays, we observed that OSBPL5 overexpression offset LMCD1-AS1 knockdown-mediated inhibition in cell proliferation, migration, invasion and EMT in NSCLC. Conclusions This paper was the first to probe the molecular regulatory mechanism of OSBPL5 involving the LMCD1-AS1/miR-526b-3p axis in NSCLC and our results revealed that the LMCD1-AS1/miR-526b-3p/OSBPL5 axis facilitates NSCLC cell proliferation, migration, invasion and EMT, which may offer a novel therapeutic direction for NSCLC.